2015
DOI: 10.1038/srep16659
|View full text |Cite
|
Sign up to set email alerts
|

A novel violet/blue light-emitting device based on Ce2Si2O7

Abstract: Rare-earth silicates are highly efficient materials for silicon-based light sources. Here we report a novel light-emitting device based on Ce2Si2O7. Intense violet/blue electroluminescence was observed, with a turn-on voltage of about 13 V. The violet/blue emission is attributed to 4f–5d transitions of the Ce3+ ions in Ce2Si2O7, which are formed by interfacial reaction of CeO2 and Si. Electroluminescence and photoluminescence mechanisms of the Ce2Si2O7 light-emitting device are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In addition to these, many low-intensity peaks were also observed but are difficult to recognize. All these features match beautifully with the characteristic Raman spectra of rhombohedral BiFeO 3 phase, which shows good correlation with XRD results . Again, Figure b depicts the Raman scattering spectra of MCeO 2 nanorods, where the sharp tower-like polarization band located at 464 cm –1 represents the F 2g symmetric vibration mode of cubic fluorite CeO 2 .…”
Section: Resultssupporting
confidence: 72%
“…In addition to these, many low-intensity peaks were also observed but are difficult to recognize. All these features match beautifully with the characteristic Raman spectra of rhombohedral BiFeO 3 phase, which shows good correlation with XRD results . Again, Figure b depicts the Raman scattering spectra of MCeO 2 nanorods, where the sharp tower-like polarization band located at 464 cm –1 represents the F 2g symmetric vibration mode of cubic fluorite CeO 2 .…”
Section: Resultssupporting
confidence: 72%
“…Here a strong blue emission peak and week one centered at 415 and 439 nm respectively, are mainly associated with the defect levels localized between the O 2p and Ce 4f band levels. The other weak blue emissions centered at 467, 481, and 495 are possibly due to the surface defects and Ce 3+ states. ,, Pure BiOI shows an emission peak nearly at 420 nm consistent with the emission characteristic of bismuth oxyiodide . From Figure a, it was found that 40% BiOI–CeO 2 exhibits a stronger PL intensity peak than the neat CeO 2 as well as BiOI suggesting faster recombination of charge carriers in the composite.…”
Section: Resultsmentioning
confidence: 60%
“…Nevertheless, numerous studies have demonstrated the efficient emission of Ce 3+ in samples deposited from CeO 2 targets. [15][16][17] Unfortunately, depositing from CeO 2 target requires a post-growth annealing step at high temperature to form optically active Ce 3+ ions which could generate Ce clusters due to the high thermal budget. Considering the above mentioned arguments, we believe that doping the SiO X N Y host matrix with Ce appears to be an interesting approach for achieving efficient cerium emission.…”
Section: Introductionmentioning
confidence: 99%
“…That is why recent researchers have turned to investigate host matrices easily integrable on silicon such as silicon oxide. 14,15 Regarding the Ce doped devices devoted to light emitting devices on silicon, the feasibility of a CeO 2 and Ce 2 Si 2 O 7 LEDs has been demonstrated, 16,17 while a Ce-doped SiO x matrix shows a strong emission of the Ce 3+ ion. 18,19 Unfortunately, it exists some major drawbacks hampering such applications.…”
Section: Introductionmentioning
confidence: 99%